Harga: Balutan Tradisi - Nur Habbibah Rachmi (Program Studi Manajemen, 2020)
The purpose of this study is to reveal the meaning of prices implemented through the tradition of the Gresik community. This research is a qualitative study using a phenomenological approach, data collected through interviews and informant observation. The results of the study found three meanings of prices, the first price as an effort to establish faith, the second price as a form of togetherness, the third price is not material. The existence of cultural values ​​seems to dismiss the notion that states if the price is closely related to the material and profits